Agroecology and school garden as tools for environmental education and natural food production / Agroecologia e horta escolar como ferramentas de educação ambiental e produção de alimentos naturais - Lucas Francisco da Silva; Rubens Pessoa de Barros; Rodrigo Almeida Pinheiro; Jecilãine Efigênia da Silva; Maria Jéssica dos Santos Cabra; Jéssika Silva de Lima (Universidade Estadual de Alagoas, 2020)
The school that adopts environmental education as an instrument of awareness should guide the student to seek values that lead to a harmonious routine with the environment in which it operates. And, in this sense, the school garden can act as a field of teaching and learning within the school, and can be accessed at many times by the students and teachers of the institution who adhered to the technique as a teaching tool. Given the above, this work aimed to use agroecological techniques associated with environmental education for the construction of a school garden in the Deputado José Lúcio de Melo Municipal School. The action was developed from January to March 2019. For the construction of the garden, soil management, fertilization and subsequent sowing of seeds and seedlings in the flowerbeds were carried out. Given the implementation of the school garden, it was noticed that opposing to the conventional model, the agroecological techniques have a potential for the production of organic food, thus ensuring the maintenance and preservation of the environment used for the garden. The process becomes fundamental for the teaching and learning of students, and can be verified according to the answers obtained from the questionnaire about the experiences during the process of construction and monitoring of the garden until the harvest period. Therefore, it is concluded that the agroecological techniques associated with teaching practices in environmental education were fundamental for the process of implementation of the school garden.